Analisis Isi Kurikulum Pendidikan Agama Islam di Tingkat SMP - Pratama, Andika; Ginting, Nurman (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
The purpose of this article is to analyze the contents of the Islamic Religious Education (PAI) curriculum in Junior High Schools, including the boundaries and topics taught both in Junior High Schools. The author as a whole reviews the curriculum, syllabus, and textbooks related to teaching PAI, as well as the role of Islamic Religious Education in public schools. The research method used is descriptive with qualitative analysis. The data collection methods used by the author are observation, interviews and documentation. In this study there are three stages that must be carried out in analyzing qualitative research data, namely (1) data reduction (data reduction); (2) data display (data display); and (3) drawing conclusions and verifying (conclusion drawing/verifying). The results of the analysis show that PAI teaching is limited to a predetermined time, only given for 2 lesson hours. In this case, it is important that there is a touch or enthusiasm from the school to continue to try to carry out PAI learning to the fullest, students are able to understand, practice, and interpret the values ​​in a concrete way from what they have learned, not just cognitive and rote. Teachers have not studied the vision contained in the curriculum, especially the ideas, thoughts and main objectives contained in the curriculum. These core ideas may come from the philosophy, theory, and political foundations behind the curriculum. Furthermore, the teachers at Dharma Utama Middle School have not analyzed the advantages and disadvantages of the implemented curriculum